KEMAMPUAN MENULIS TEKS ULASAN PESERTA DIDIK KELAS VIII SMP PANCASILA PAL IX KABUPATEN KUBU RAYA - Fadilah, Fadilah Dila; Heryana, Nanang; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the ability to write review texts for the short film "Lima Detik" by Ja'far Ash by grade VIII students of SMP Pancasila Pal IX Kubu Raya Regency based on aspects of structure, language, and writing of EBI. This research uses descriptive research methods with quantitative research forms. Data collection was carried out through a test of writing the review text of the short film "Five Seconds" by Ja'far Ash. The results of this study showed that the ability to write student review texts was classified into the good category, with an average score of 71,33. The ability to write review texts based on structural aspects obtained an average score of 68,75 with sufficient categories, based on linguistic aspects obtained an average score of 97,91 with very good categories, and based on the writing of EBI obtained an average score of 58,33 with sufficient category. Based on the distribution table, the percentage of the value of the ability to write review text shows the very good category (16,67%), good category (54,17%), sufficient category (16,67%), and less category (12,5%). Through this research, it is hoped that teachers can Indonesian find out the ability of students, especially in writing review texts. After knowing the abilities of students, teachers can further improve the effectiveness of learning to write review texts